2016
DOI: 10.1002/pc.24099
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physico‐mechanical and thermo‐mechanical analysis of alumina filled needle‐punch nonwoven jute epoxy composites

Abstract: In the present study, needle-punch nonwoven jute fiber reinforced epoxy composites are fabricated by compression molding techniques by varying alumina ceramic particulates (0-15 wt%) in the composites. The physical tests are studied such as void content, hardness, and water absorption analysis and mechanical tests are performed such as: tensile strength, impact strength, and fracture toughness, respectively. The results indicated that with the addition of 5 wt% of alumina particulate to the unfilled needle-pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…The inclusion of PLSS improved the loss modulus of EPP0 composite from 49.6 MPa to 85.6 MPa, 90.7 MPa, and 96.3 MPa for 5 wt%, 10 wt%, and 15 wt%, respectively. The present results are consistent with previous research on alumina filled jute-epoxy composite (Patnaik and Nayak, 2016) and graphene oxide filled carbon-epoxy composite (Adak et al 2018).…”
Section: Temperature (°C) Loss Modulus (Mpa)supporting
confidence: 94%
See 1 more Smart Citation
“…The inclusion of PLSS improved the loss modulus of EPP0 composite from 49.6 MPa to 85.6 MPa, 90.7 MPa, and 96.3 MPa for 5 wt%, 10 wt%, and 15 wt%, respectively. The present results are consistent with previous research on alumina filled jute-epoxy composite (Patnaik and Nayak, 2016) and graphene oxide filled carbon-epoxy composite (Adak et al 2018).…”
Section: Temperature (°C) Loss Modulus (Mpa)supporting
confidence: 94%
“…The visco-elastic properties of short glass fiber reinforced polypropylene composites were enhanced when calcite was added (Senturk et al 2018). Similarly, various fillers like granite powder (Pawar et al 2015), alumina (Patnaik and Nayak 2016), fly ash cenosphere (Satapathy and Kothapalli 2017), nano ZnO and TiO2 (Prasob and Sasikumar 2018), and cork (Karduman 2018) showed a positive response on the thermal behavior of composites.…”
Section: Introductionmentioning
confidence: 96%
“…% the hardness, improved and estimated as 28.7, 33.3, and 35.2 H V , respectively. Similar findings also reported by Patnaik and Nayak [17] that with the addition of alumina powder in jute fabric-based polymer composite hardness increased. It is evident that the compressive load applied through the indenter press the matrix and the reinforcements together which provides a resistance.…”
Section: Mechanical Testssupporting
confidence: 90%
“…It was also found that increasing the fiber content of the polymer composite further increased the hardness of the composite. Kumar Patnaik and Nayak 77 did the physico-mechanical and thermo-mechanical analysis of alumina filled needle punched nonwoven jute/epoxy composite. It was found that the addition of reinforcement into the matrix improved its hardness and further addition of alumina filler also improved the hardness of the polymer composite.…”
Section: Effects Of Reinforced Architecture On Static Performance Of ...mentioning
confidence: 99%